(NnIKOLAJ (B.(NqKOWLEWI^ (B.(NmQSKOWSKIJs (NMONOGRAFIQs - (Nz(B.(Nk(B.(NgULINSKAQs (NnIKOLAJ qKOWLEWI^ mQSKOWSKIJs ((NmOSKWAs (NmUZYKAs, 1981)
(NmQSKOWSKIJ SRAZU NA[EL PUTX (B,(NPO KOTOROMU PRI[EL W \POHU(B.s
Keywords: (NmONOGRAFIQs